PEMAAFAN DALAM TINDAK PENGANIAYAAN - Fitriyatinur, Qurnia (Widya Warta, 2021)
This study discusses forgiveness and its relation to criminal acts of persecution from the legal and psychological aspects, so it is hoped that there will be a new discourse in law that puts forward normative aspects and at the same time it does not forget the substantive aspects of the law. By examining victims of abuse that were tailored to the needs of research and the substantive linkages between law and psychology, it was elaborated in relation to efforts to discourse on new laws in acts of persecution based on a psychological approach, in this case forgiveness. Fundamental problems in the field of law in Indonesia are law-making and law enforcement. One alternative that can be done is to forgive in an action. Forgiveness is basically the choice of someone who becomes a victim in an action or an offense. If it is reviewed more deeply, especially on the psychological aspect, forgiveness is a way that can be used to reconcile the relationship between the perpetrators of acts of persecution and victims of persecution.